Impaired decision-making after traumatic brain injury: The Iowa Gambling Task. (July 2014) - Cotrena, Charles; Branco, Laura Damiani; Zimmermann, Nicolle; Cardoso, Caroline Oliveira; Grassi-Oliveira, Rodrigo; Fonseca, Rochele Paz
Abstract Summary: The aim of the present study was to use the Iowa Gambling Task (IGT) to investigate differences in decision-making (DM) between patients who sustained TBI and healthy subjects, while controlling for age, education and gender. Methods: A hundred and ten participants, half of whom had severe or mild TBI, completed the IGT. Results: Differences between control participants and patients with TBI were found regarding total net score, block score, number of selections from each deck and classification of performance as impaired or unimpaired. No significant differences in IGT performance were found between patients with and without frontal lesions and between patients with mild and severe TBI. Conclusions: Results indicate poor DM on the IGT in patients with TBI, regardless of lesion location and severity. The instrument proved to be equally sensitive to both frontal and extrafrontal lesions and did not differentiate between patients with mild and severe TBI.